2020
DOI: 10.5713/ajas.19.0473
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary probiotic, liquid feed and nutritional concentration on the growth performance, nutrient digestibility and fecal score of weaning piglets

Abstract: Objective: This study was conducted to investigate the effects of dietary probiotic blend and liquid feed program at different nutritional densities on growth performance, nutrient digestibility, fecal score of weaning piglets.Methods: A total of 120 weaning pigs with an initial body weight of 7.05±0.93 kg per pig (21 days of age) were randomly allocated into 1 of the following 8 dietary treatments (3 replicates per treatment with 5 pigs per replicate) in a 2×2×2 factorial arrangement (nutrition levels: appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…The probable reason is that the palatability of piglets was improved by increasing the amount of corn starch. More dry matter intake had no effect on FCE, even though it might have caused the growth of weaned piglets [27], which was consistent with our results. In addition, the co-treatment group with both higher crude protein digestibility and crude fat digestibility was Treatment Diets B and C (132.5 and 300.0 g/kg MG).…”
Section: Discussionsupporting
confidence: 92%
“…The probable reason is that the palatability of piglets was improved by increasing the amount of corn starch. More dry matter intake had no effect on FCE, even though it might have caused the growth of weaned piglets [27], which was consistent with our results. In addition, the co-treatment group with both higher crude protein digestibility and crude fat digestibility was Treatment Diets B and C (132.5 and 300.0 g/kg MG).…”
Section: Discussionsupporting
confidence: 92%
“…Dietary supplementation with ZnO and AGP has been shown to be capable of suppressing the colonization of pathogenic bacteria in the intestine and decreasing post-weaning diarrhea ( Nofrarías et al., 2006 ; Shelton et al., 2011 ; Cho et al., 2015 ). In this trial, there were more than 37% of piglets with fecal score ≥2 which might be ascribed to the high crude protein level (20%) and the high content of soybean meal that have been approved in the previous studies ( Li et al., 1990 ; Wen et al., 2018 ; Zhang et al., 2020 ). Notably, the percentage of piglets with fecal score at 2, or ≥2 were lower in the PC than in the NC and SDCP groups, but was not different between the PC and SDPP groups, which was consistent with the results of growth performance.…”
Section: Discussionmentioning
confidence: 92%
“…Pigs fed PRO tended to have improved ATTD of CP (87.25 vs. 84.13%; p < 0.10). Several studies have shown that the addition of Bacillus to pig feed could improve growth performance or reduce the incidence of diarrhea [16,23]. However, some previous studies failed to observe such positive effects on growth performance [24][25][26].…”
Section: Growth Performance and Nutrient Digestibilitymentioning
confidence: 99%